Effect of direct-fed microbial (dfm) supplements on general performance of newborn awassi lambs - Abdelrahman, Mutassim Mobamed (2010)
Accelerating the onset of weaning of pre-ruminant can he achieved by enhancing the development of rumen microorganisms using direct fed microbial (DFM).
Includes references.
1
Keywords: Lambs -- Breeding; Lambs -- Feeding and feeds; Microbial products